Assessment of Fe, Ni, Zn, Cu, Cr, and Cd Migration in Soil Profiles Affected by Open Dump Leachate in Tanjero area - Salh, Qadri Karim; Abdalla, Zhino Othman; Rashid, Khasraw Abdulla; Sheikh-Abdullah, Shuela Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2023)
The properties of an open dump area are important to the application of the elements to the soils and their migrations through soil depth; therefore this study was investigated to evaluate the migration of elements in an open dump area. Soil samples were taken from three soil profiles, one of them was at an open dump site, and the second and third profiles were taken at different distances from the open dump site. In total eighteen soil sample were collected. Some soil physical and chemical properties were determined for each horizon. Total concentrations of Fe, Ni, Zn, Cu, Cr, and Cd were determined in each soil sample. The results indicated that the Fe had the highest value and the Cd had the lowest values in all soil samples. The orders of profiles for the total heavy (Ni, Cd, and Cr) metals were as follows: Profile1 > profile3 > profile 2. The order of profiles for the total heavy (Zn and Cu) metals was as follows: Profile 1 > profile 2 > profile 3. The mean value of total Ni ranged between 9.17 and 11.13, Cd between 0.29 and 0.37, Cr between 2.67 and 3.36, Zn between 6.90 and 17.23, and Cu between 4.90 and 12.52. The highest amount of total Ni, Cd, Cr, Zn, and Cu were observed in open dump area (profile 1) with the mean value (11.13, 0.37, 3.36, 17.23, and 12.52) respectively, compared to the profile 2 and 3. In general, the heavy metals did not show a specific pattern of distribution with depth in the three soil profiles, because there are many factors affecting migration of heavy metals in soil depth. In both profile 2 and 3, some of the heavy metals migrated in soil depth.
Keywords: Heavy metals; Soilprofile; Open dumparea; Soil properties